2020
DOI: 10.1111/epi.16472
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antiseizure drug‐related adverse reactions from the electronic health record using the common data model

Abstract: Objective: Antiseizure drugs (ASDs) are known to cause a wide range of adverse drug reactions (ADRs). Recently, electronic health care data using the common data model (CDM) have been introduced and commonly adopted in pharmacovigilance research. We aimed to analyze ASD-related ADRs using CDM and to assess the feasibility of CDM analysis in monitoring ADR in a single tertiary hospital. Methods: We selected five ASDs: oxcarbazepine (OXC), lamotrigine (LTG), levetiracetam (LEV), valproic acid (VPA), and topirama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Although the increased detection of ADRs after incorporation of a prospective pharmacovigilance program is well documented, these programs are unfortunately not the standard in all hospitals. Developing standardized EMR alerts or reports to detect ADRs requires time and infrastructure 3,6,16,20,21 . In addition, personnel, typically a clinical pharmacist, are needed to evaluate automated EMR reports and investigate potential ADRs 20,22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the increased detection of ADRs after incorporation of a prospective pharmacovigilance program is well documented, these programs are unfortunately not the standard in all hospitals. Developing standardized EMR alerts or reports to detect ADRs requires time and infrastructure 3,6,16,20,21 . In addition, personnel, typically a clinical pharmacist, are needed to evaluate automated EMR reports and investigate potential ADRs 20,22 …”
Section: Discussionmentioning
confidence: 99%
“…Developing standardized EMR alerts or reports to detect ADRs requires time and infrastructure. 3,6,16,20,21 In addition, personnel, typically a clinical pharmacist, are needed to evaluate automated EMR reports and investigate potential ADRs. 20,22 Although personnel, EMR tools, and usability are very important, education and a positive culture of ADR reporting can be invaluable in increasing ADR reporting rates.…”
Section: Discussionmentioning
confidence: 99%
“…Our research has a great significance that we effectively utilized the big data from the integrated model, the CDM, within one of the biggest national hospitals in South Korea. CDM research has been expanded in its scope and conducted worldwide for the vitalization of medical research 19 . With the use of commonly formatted EMR records, our research successfully reflects the real-world challenges in the context of coronavirus.…”
Section: Discussionmentioning
confidence: 99%
“…Levetiracetam (LEV) is a commonly used antiepileptic medication for the prophylaxis and treatment of focal and generalized seizures due to its efficacy, tolerance, good pharmacokinetic profile, and relatively benign adverse effects [1][2][3]. In an open-label placebo-controlled study by Abou-Khalil et al, adverse effects observed in 10% or more of users at individualized doses of 1,000-3,000 mg/day were asthenia, nausea, dizziness, somnolence, nervousness, anorexia, psychiatric side effects as well as other tolerable side effects [4].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other similarly used anti-seizure medications, severe adverse effects like hepatotoxicity, hemodynamic imbalances, pancytopenia, or significant drug interactions are not usually associated with its use [5][6]. However, thrombocytopenia has been reported with LEV use in several clinical settings and patient populations, oftentimes along with other thrombocytopenia-inducing medications [1,[7][8][9][10][11][12]. Here, we report a case of acute significant thrombocytopenia that developed following LEV use in the setting of status epilepticus in an anticoagulated immunocompetent patient.…”
Section: Introductionmentioning
confidence: 99%